Clinical ethicists' perspectives on organisational ethics in healthcare organisations. Issue 5 (30th April 2008) - Silva, D S; Gibson, J L; Sibbald, R; Connolly, E; Singer, P A
Abstract : Background: Demand for organisational ethics capacity is growing in health organisations, particularly among managers. The role of clinical ethicists in, and perspective on, organisational ethics has not been well described or documented in the literature. Objective: To describe clinical ethicists' perspectives on organisational ethics issues in their hospitals, their institutional role in relation to organisational ethics, and their perceived effectiveness in helping to address organisational ethics issues. Design and Setting: Qualitative case study involving semi-structured interviews with 18 clinical ethicists across 13 health organisations in Toronto, Canada. Results: From the clinical ethicists' perspective, the most pressing organisational ethics issues in their organisations are: resource allocation, staff moral distress linked to the organisation's moral climate, conflicts of interest, and clinical issues with a significant organisational dimension. Clinical ethicists were consulted in particular on issues related to staff moral distress and clinical issues with an organisational dimension. Some ethicists described being increasingly consulted on resource allocation, conflicts of interest, and other corporate decisions. Many clinical ethicists felt they lacked sufficient knowledge and understanding of organisational decision-making processes, training in organisational ethics, and access to organisational ethics tools to deal effectively with the increasing demand for organisational ethics support. Conclusion: Growing demand for organisational ethics expertise in healthcare institutions is reshaping the role of clinical ethicists. Effectiveness in organisational ethics entails a re-evaluation of clinical ethics training to include capacity building in organisational ethics and organisational decision-making processes as a complement to traditional clinical ethics education.